Fun home : a family tragicomic - Bechdel, Alison (London : Jonathan Cape, 2006)
DISCOVER the BESTSELLING GRAPHIC MEMOIR behind the SENSATIONAL LONDON MUSICAL The award-winning musical adaptation that took America by storm now playing to five star reviews at the Young Vic | `A sapphic graphic treat' The TimesA moving and darkly humorous family tale, pitch-perfectly illustrated with Alison Bechdel's gothic drawings.
Old father, old artificer -- A happy death -- That old catastrophe -- In the shadow of young girls in flower -- The canary-colored caravan of death -- The ideal husband -- The antihero's journey.
Fiction
ENH
Keywords: Bechdel, Alison, -- 1960-; Cartoonists -- United States -- Comic books, strips, etc; English language